Principles of structural geology on rocky planets - Klimczak, Christian; Byrne, Paul K.; Şengör, Celâl; Solomon, Sean C. (Canadian Science Publishing, 2019)
Although Earth is the only known planet on which plate tectonics operates, many small- and large-scale tectonic landforms indicate that deformational processes also occur on the other rocky planets. Although the mechanisms of deformation differ on Mercury, Venus, and Mars, the surface manifestations of their tectonics are frequently very similar to those found on Earth. Furthermore, tectonic processes invoked to explain deformation on Earth before the recognition of horizontal mobility of tectonic plates remain relevant for the other rocky planets. These connections highlight the importance of drawing analogies between the rocky planets for characterizing deformation of their lithospheres and for describing, applying appropriate nomenclature, and understanding the formation of their resulting tectonic structures. Here we characterize and compare the lithospheres of the rocky planets, describe structures of interest and where we study them, provide examples of how historic views on geology are applicable to planetary tectonics, and then apply these concepts to Mercury, Venus, and Mars.
Keywords: Lithosphere; Planets--Geology; Structural; Planetary science; Geology, Structural; Geology